Relationship Ki-67 and BCL-2 in gastrointestinal lymphomas - Hatice E. PEŞDERELİ,; Kemal H. GÜLKESEN,; Gülgün ERDOĞAN,; Mustafa T. GELEN,; Gülten KARPUZOĞLU,; İnci SÜLEYMANLAR,; Canan F. SARGIN, (Turkish Journal of Gastroenterology, 2019)
-